Conflict management styles of teachers teaching at Muhammadiyah Islamic Boarding schools in Tasikmalaya district, Indonesia - Putra, Andri (Institute of Education, International Islamic University Malaysia, 2014)
The main focus of the study describes the conflicts that exist in Muhammadiyah Islamic boarding schools in Tasikmalaya regency, Indonesia. The study provides information of various levels of conflict experienced by teachers teaching at Muhammadiyah Islamic boarding schools in Tasikmalaya, Indonesia, the study also discussed the five conflict management styles adopted by teachers teaching at those schools. These five conflict management styles are; Avoiding style, Dominating style, Compromising style, Obliging style, and Integrating style. This study also describes at what level were each conflict management style used by teachers in managing their conflict within their school environment. Questionnaires were the main tool of the study as the data was collected by using survey methods. One hundred and twenty two (122) teachers were chosen as respondents of the study. The data gathered from the survey was analyzed using descriptive analysis, Independent Sample T-test, One Way ANOVA, and MANOVA statistics of the SPSS-Version 18.0 programme. The findings indicate that majority of teachers experienced moderate level of conflict. In term of the level of conflict the study found that female teachers experienced higher level of conflict compared to male teachers, in term of age and year of experiences found that there are no statistically differences in the level of conflict experienced by teachers. Additionally, regarding conflict management styles practices, it is found that both integrating and compromising styles are highly practiced while obliging, avoiding, and dominating style are moderately practiced by teachers at those Muhammadiyah Islamic boarding schools in Tasikmalaya, Indonesia. Furthermore, it is found that there is no statistically differences between male and female in practicing those five conflict management styles. On the other hand, there are statistically significant differences in practicing those five conflict management styles based on teachers teaching experience. As this study was conducted in Muhammadiyah Islamic boarding schools in Tasikmalaya, it is recommended that similar studies to be conducted in other cities or countrywide in order to obtain more general and reliable result.